Talking About Looking: Three Approaches to Interviewing Carers of People With Rheumatoid Arthritis About Information Seeking. (July 2016) - Lee, Richard Philip; Thompson, Ben; Whybrow, Paul; Rapley, Tim
Given the profusion of illness-related information, in this article, we consider how talking about information seeking—and in particular Internet use—is difficult, not because it is necessarily a highly sensitive topic (though it may be), but rather due to the unusual and unfamiliar situation of talking about information seeking. Drawing on interviews conducted as part of a study on the educational needs of carers of people with rheumatoid arthritis, we compare three types of interview for understanding online information seeking: interviews (recall), researcher-led observation (joining participant at the computer), and diaries. We discuss the strengths and weaknesses of each approach and discuss how changing interview questions and the form of interaction can help to produce different types of data, and potentially more meaningful insights. Of the three approaches, conducting interviews with participants while looking at a computer (talking while looking) offered the best opportunities to understand Internet-based information seeking.